2019
DOI: 10.3389/fphar.2019.00096
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Nonsteroidal Anti-inflammatory Drugs and Reducing Opioids or Paracetamol in the Management of Acute Renal Colic: Based on Three-Stage Study Design of Network Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Currently, although non-steroidal anti-inflammatory drugs (NSAIDs) were recommended for acute renal colic in the 2018 European Association of Urology guidelines, there are no specific NSAIDs and no specific routes of administration in this guideline. The clinical practice of advocating intravenous opioids as the initial analgesia is still common out of the fear of adverse events from NSAIDs. Objectives: To comprehensively assess the efficacy and safety of NSAIDs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(55 reference statements)
0
6
0
2
Order By: Relevance
“…showed that in the most studies, NSAIDs like ibuprofen or ketorolac were the better choice of acute renal colic management because of lower adverse effects compared to opioids alone or combination of both. [ 11 ] Different kinds of administration, different dose of morphine, and different kind of NSAIDs used in this systematic review illustrate the different findings.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…showed that in the most studies, NSAIDs like ibuprofen or ketorolac were the better choice of acute renal colic management because of lower adverse effects compared to opioids alone or combination of both. [ 11 ] Different kinds of administration, different dose of morphine, and different kind of NSAIDs used in this systematic review illustrate the different findings.…”
Section: Discussionmentioning
confidence: 96%
“…revealed that in the most of the studies, NSAIDs were more effective in more than 50% renal colic pain relief than opioids, combination of both or placebo and the superiority of NSAIDs could be its direct effect on inhibition of cyclooxygenase enzyme, but the combination therapy had significant priority compared to monotherapy in patients with uncontrollable renal colic pain with NSAIDs alone also in comparison of all outcomes including pain variance at 30 min, rescue analgesic requirements and acute adverse effects. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of NSAIDs also has advantages and disadvantages. [ 7 8 ] These drugs inhibit prostaglandins and as mentioned above, prostaglandins play an important role in the development of renal colic. Disadvantages of these drugs include increasing the chances of kidney failure and gastrointestinal bleeding.…”
Section: Introductionmentioning
confidence: 99%